Prisoners and Pleading - Richard H. Frankel; Alistair E. Newbern (Washington University Law Review, 2017)
Last year, prisoners filed nearly 27,000 civil rights actions in federal court. More than 92 percent of those actions were filed pro se. Pro se prisoners frequently use—and in many districts are required to use— standardized complaint forms provided by the federal judiciary. These standard forms were created in the 1970s at the recommendation of a committee of federal judges seeking to more effectively manage prisoner litigation and reduce its burdens on the federal courts. Although complaint forms have been in use for nearly forty years and are now commonplace in almost every federal district, no one, until now, has recognized the extent to which these forms may diverge from or misrepresent the law. In this paper, we collect and analyze every form complaint used by the federal district courts. Our results indicate that, while form complaints can be helpful to pro se prisoners and the courts, many impose requirements that are inconsistent with governing law. First, many complaints direct prisoners to plead facts that the law does not require them to plead. Second, many complaints prohibit or discourage prisoners from pleading facts necessary to survive a motion to dismiss. Third, some complaints require plaintiffs to plead legal conclusions, using language that may confuse unsophisticated prisoners and cause them to make inadvertent but significant legal errors. These flaws can impose serious unintended consequences on prisoners, including unwarranted dismissal of their complaints. They can also impose additional work on judges and court staff who must reconcile discrepancies between the court-provided forms and governing law. To address the concerns raised by our study, we provide a model form complaint that accurately reflects governing law and helps courts more efficiently review pro se prisoner complaints and recognize potentially meritorious claims.
Keywords: Prisoner; Pro se; form complaint; federal courts; prisoner litigation; Prison Litigation Reform Act; Bell Atlantic Corp. v. Twombly; Ashcroft v. Iqbal; prisoner form complaints